Social Welfare Policies and Poverty Reduction: The Role of Family Support Programs - Lina Saleh; Ahmad Khalil (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This article explores the effectiveness of social welfare policies in reducing poverty, focusing on family support programs such as childcare assistance, food security, and housing subsidies. Using case studies from various countries, the study assesses how these programs impact economic stability and improve quality of life for low-income families. Results indicate that comprehensive family support programs are critical for poverty alleviation and social equity.